Faktor Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntansi (PPAK) di Indonesia - Yanti, Ullifah (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Professional Accounting Education (PPAK) plays an important role in equipping students majoring in accounting to become experts in the field of accounting. The aim of this research is to determine how certain factors influence accounting students' desire to take part in a professional accounting program, as well as evaluate the impact of the academic environment on accounting students' intentions to complete PPAK. This research method uses a